Skyflower: Hydrolea corymbosa - Lyn A. Gettys; Carl J. Della Torre (EDIS)
Skyflower is a native wetland plant that produces brilliant blue flowers and can be found throughout Florida. This 4-page facts sheet details skyflower biology, distribution and habitat, propagation, and uses. Written by Lyn A. Gettys and Carl J. Della Torre III, and published by the UF Department of Agronomy, July 2015.